Governance and development: a perspective on Malaysia’s New Economic Policy (1971-1990) - Eisa, Garout Suliman (International Institute for Muslim Unity, International Islamic University Malaysia, 2007)
The Malaysian achievement in development and poverty alleviation was generally recognized throughout the World as a distinguished one. This paper argues that the system of governance that has been introduced and maintained by the country’s elites can be identified as the main explanatory variable behind these successes. The consociation form of democracy as an approach to governance was well adapted to accommodate the country’s ethnic diversity and help maintain political stability. The resulting political stability was exploited for the design and implementation of effective development programmes which helped attract foreign investment, transfer technology and alleviate poverty. The New Economic Policy was the most basic * Garoutprogramme that addressed the country’s development problems and laid the groundwork for development and poverty alleviation. Though it may not be ideal in terms of textbook models of liberal democracy, yet governance in Malaysia is better than most developing countries in terms of performance. Consequently, other developing countries, particularly Muslim countries whose social structure and development problems are similar to that of Malaysia, can learn lessons in better governance in the form of politics of racial accommodation in place of confrontation as well as in design and implementation of effective programmes meant to address specific development goals.